Integration of technology in the mechatron module of liquid dosing - Yasychev, Vladyslav; Butyk, Taras; Kryvoplias-Volodina, Liudmyla (My University, 2023)
The influence of individual parameters on the accuracy of productdose formation was determined during physical and mathematical modeling. We have found ways to ensure the necessary distribution of compressed air pressure, subject to compliance with the specified performance of the dispenser. Research results make it possible to improve the operation of dosing systems for liquid products with high dosing accuracy. The control system is formed on the basis of electro-pneumatic complexes. The control model with dosing operating modes is substantiated. It was established that the consumption of compressed air will depend on the value of the input main pressure P (0.05... 0.4 MPa). The consumption of the product was in the range of 1 ml to 50 ml with a feeder volume of 2.25 l. A mathematical model of the dosing process of liquid products (noncarbonated drinking water, milk, juice) has been developed. Boundary conditions took into account the influence on the formation of the product dose from the programmed current values in mA (with an accuracy of 0.001 mA) in relation to the standard scale Imin, Imax=4..20 mA. An analytical description of individual stages of the dosing process with further analysis of individual stages and accepted assumptions was formed. Tests of the experimental sample of the dispenser showed the accuracy of the repetitions of the dose extrusion (limits ± 0.035% and 0.8%) from the set value of the dose mass up to 50 ml during the change and the initial liquid level in the reservoir of the dispenser feeder.

За допомогою фізичного та математичного моделювання визначено вплив окремих параметрів на точність формування дози продукту. Знайдено шляхи забезпечення необхідного розподілу тиску стисненого повітря за умови дотримання заданої продуктивності дозатора. Результати досліджень дозволяють удосконалити роботу систем дозування рідких продуктів з високою точністю дозування. Система керування сформована на основі електропневматичних комплексів. Обґрунтовано модель керування режимами роботи дозатора. Встановлено, що витрата стисненого повітря буде залежати від величини вхідного магістрального тиску Р (0,05...0,4 МПа). Витрата продукту знаходилась в діапазоні від 1 мл до 50 мл при об'ємі живильника 2,25 л. Розроблено математичну модель процесу дозування рідких продуктів (негазована питна вода, молоко, сік). Граничні умови враховували вплив на формування дози продукту запрограмованих значень струму в мА (з точністю до 0,001 мА) відносно стандартної шкали Imin, Imax=4..20 мА. Сформовано аналітичний опис окремих етапів процесу дозування з подальшим аналізом окремих етапів та прийнятих допущень. Випробування експериментального зразка дозатора показали точність повторень видавлювання дози (межі ± 0,035% і 0,8%) від заданого значення маси дози до 50 мл протягом зміни і початкового рівня рідини в резервуарі живильника дозатора.
Keywords: кафедра мехатроніки та пакувальної техніки; dosing; air lift system; excess pressure; feedback; dosing accuracy; дозування; система підйому повітря; надлишковий тиск; зворотній зв'язок; точність дозування